2016
DOI: 10.4236/jbise.2016.97029
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Beige Adipocytes Induced from White Adipocytes by <i>Kikyo</i> Extract

Abstract: Beige adipocytes are believed to have a high ability to consume fat. As such, compounds capable of inducing the development of beige adipocytes may be useful as drugs for anti-obesity and antitype 2 diabetes. However, the true nature of beige adipocytes remains unclear. The purpose of this study is to confirm whether or not white adipocyte can differentiate to beige adipocytes and to clarify the characteristics of beige adipocytes. We first searched for an inducer of beige adipocytes and found that kikyo extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Food components with noradrenaline-like structures can stimulate β3-AR, and their continuous intake may induce brown or beige adipocytes. We reported that Kikyo, the constituents of Bofutsushosan (Chinese medicine), contain components that transdifferentiate mouse white adipocytes into beige adipocytes [50]. Another group reported that p-synephrine extracted from Citrus unshiu Marcow contains a component that converts to beige adipocytes [51].…”
Section: Preventive Treatment Of Metabolic Syndrome With Thermogenic Fatmentioning
confidence: 99%
“…Food components with noradrenaline-like structures can stimulate β3-AR, and their continuous intake may induce brown or beige adipocytes. We reported that Kikyo, the constituents of Bofutsushosan (Chinese medicine), contain components that transdifferentiate mouse white adipocytes into beige adipocytes [50]. Another group reported that p-synephrine extracted from Citrus unshiu Marcow contains a component that converts to beige adipocytes [51].…”
Section: Preventive Treatment Of Metabolic Syndrome With Thermogenic Fatmentioning
confidence: 99%
“…Leptin and adiponectin enhance the capacity of glucose consumption by increasing the noradrenalin secretion, but TNF-α inhibits it via the inhibition of insulin receptor and transport of GLUT4 [64]. As the secretion of leptin and adiponectin is decreased and the secretion of TNF-α is increased in white adipose tissues highly accumulating triglyceride, the glucose intake is inhibited [65]. Furthermore, the pressure on blood vessels induced by hypertrophic white adipose tissues causes an inflammatory response, and the enhanced concentration of free fatty acids in the blood by obesity causes the dysfunction of mitochondria in muscle cells and β-cells of the pancreas [66,67].…”
Section: Increase In the Rate Of Obesity Due To Changes In The Dietmentioning
confidence: 99%
“…The energy decrease results in the degradation of fatty acids via the TCA cycle to reconstitute the energy gradient. Several studies have shown that obesity and type-2 diabetes reduced by the enhancement of UCP1 in humans [20][21][22]. Capsaicin and shogaol, which are spicy ingredients of red pepper and ginger, respectively, can activate UCP1 via the TRPV1 receptor, producing heat.…”
Section: Foods That Decrease the Risk Of Lifestyle Diseasesmentioning
confidence: 99%